LANA-Mediated Recruitment of Host Polycomb Repressive Complexes onto the KSHV Genome during De Novo Infection. - Zsolt Toth; Bernadett Papp; Kevin Brulois; Youn Jung Choi; Shou-Jiang Gao; Jae U Jung (PLoS Pathogens, 2016)
One of the hallmarks of the latent phase of Kaposi's sarcoma-associated herpesvirus (KSHV) infection is the global repression of lytic viral gene expression. Following de novo KSHV infection, the establishment of latency involves the chromatinization of the incoming viral genomes and recruitment of the host Polycomb repressive complexes (PRC1 and PRC2) to the promoters of lytic genes, which is accompanied by the inhibition of lytic genes. However, the mechanism of how PRCs are recruited to the KSHV episome is still unknown. Utilizing a genetic screen of latent genes in the context of KSHV genome, we identified the latency-associated nuclear antigen (LANA) to be responsible for the genome-wide recruitment of PRCs onto the lytic promoters following infection. We found that LANA initially bound to the KSHV genome right after infection and subsequently recruited PRCs onto the viral lytic promoters, thereby repressing lytic gene expression. Furthermore, both the DNA and chromatin binding activities of LANA were required for the binding of LANA to the KSHV promoters, which was necessary for the recruitment of PRC2 to the lytic promoters during de novo KSHV infection. Consequently, the LANA-knockout KSHV could not recruit PRCs to its viral genome upon de novo infection, resulting in aberrant lytic gene expression and dysregulation of expression of host genes involved in cell cycle and proliferation pathways. In this report, we demonstrate that KSHV LANA recruits host PRCs onto the lytic promoters to suppress lytic gene expression following de novo infection.